A Spatially Periodic Solute Boundary for MT3DMS and PHT3D. Issue 3 (14th December 2016) - Laattoe, Tariq; Post, Vincent E. A.; Werner, Adrian D.
Abstract: The assumption of spatial repetition is commonly made when producing bedform scale models of the hyporheic zone. Two popular solute transport codes, MT3DMS and PHT3D, do not currently provide the necessary boundary condition required to simulate spatial periodicity in hyporheic zone transport problems. In this study, we develop a spatially periodic boundary (SPB) for solutes that is compatible with a SPB that was previously developed for MODFLOW to simulate the flow component of spatially periodic problems. The approach is ideal for simulating groundwater flow and transport patterns under repeating surface features, such as ripples or dunes on the bottom of a lake or stream. The appropriate block‐centered finite‐difference approach to implement the boundary is presented and the necessary source code modifications are discussed. The performance of the solute SPB, operating in conjunction with the groundwater flow SPB, is explored through comparison of a multi‐bedform hyporheic‐zone model with a single bedform variant. The new boundary conditions perform well in situations where both dispersive effects and lateral seepage flux in the underflow regime beneath the hyporheic zone are minimal. Abstract : Article impact statement : A method to implement a spatially periodic solute boundary in MT3DMS and PHT3D for use when simulating repeating structures.